Assessment of Bone Microarchitecture by Trabecular Bone Score to Evaluate Osteoporosis Independent of Bone Density at Mansoura University Hospital in Egypt - Saeed, Alaa Ibrahim; Elhawary, Mohammed A.; Sweed, Hala S.; Said, Salma M.S. El; Al-Araby, Mennatallah S. (South Eastern European Journal of Public Health, 2024)
Background: Osteoporosis is defined as low bone mineral density caused by altered bone microstructure, ultimately predisposing patients to low-impact fragility fractures. Osteoporosis is a global health epidemic. Over 200 million people have osteoporosis, and the incidence rate increases with age. Over 70% of those over age 80 are affected. Worldwide, there are approximately 9 million fractures per year because of osteoporosis. Bone mineral density (BMD) measured by dual X-ray absorptiometry (DXA) has been the gold standard for osteoporosis diagnosis in the absence of established fragility fractures. Trabecular bone score (TBS) is one of the most widely used assessments of bone quality. Both BMD and TBS are independent predictors of fragility fractures and are the two pillars of the World Health Organization’s (WHO) clinical definition of osteoporosis. Objective: To evaluate the ability of lumbar spine TBS to assess bone microarchitecture and osteoporosis independent of bone mineral density. Patients and methods: This cross-sectional study was conducted at Geriatric inpatient and outpatient clinic, Mansoura university Hospitals. This study was conducted on 45 elderly males (60 years and above) and postmenopausal females aged 50 years or above having one or more clinical risk factors for osteoporosis. Results: Regarding the validity of Trabecular bone score (TBS) in discriminating osteopenia/osteoporosis from normal, it was revealed that TBS at cutoff value of ≤ 1.422 can discriminate osteopenia/osteoporosis from normal with 86.4% sensitivity, and 43.5% specificity. Conclusion: TBS has a limited association with direct measurements of bone micro-architecture, can’t be used alone to diagnose primary osteoporosis and may be a useful adjunct to BMD, DEXA and QCT for evaluation of osteoporosis, fracture risk detection and prediction..